Relationship between expression mRNA gene Treg, Treg, CD4+, and CD8+ protein levels with TST in tuberculosis children: A nested case-control. (January 2021) - Farsida,; Shabariah, Rahmini; Hatta, Mochammad; Patellongi, Ilhamjaya; Prihantono,; Nasrum Massi, Muh; Asadul Islam, Andi; Natzir, Rosdiana; Dwi Bahagia Febriani, Andi; Hamid, Firdaus; Fatimah,; Akaputra, Risky; et al.
Abstract: Background: The ability of Mycobacterium tuberculosis to survive intracellularly, provides a cellular adaptive immune response played by specific T cells to defend against tuberculosis. The adaptive immune response to Bacillus of Calmette and Guerin (BCG) immunization is responded to by B cells, T Follicular B helper, T regulatory, restriction CD1, CD8 +, CD4 +, Th1, Th2, and Th17. BCG immunization can cause a tuberculin test reaction to being positive. The tuberculin test is a method for diagnosing TB infection and for screening individuals for latent infection and assessing the rate of TB infection in a given population. Methods: a nested case-control survey was conducted on patients with a diagnosis of TB and parents 0–18 years of age from 3 hospitals in Indonesia during September–November 2019 with a total sample of 69 people undergoing clinical examinations, supporting and diagnosing subjects, blood sampling 1–2 cc for examination mRNA gene Treg, Treg, CD 4+, and CD 8+, then centrifuged at 3000 rpm for 10 min to support blood cells and serum. Results: There was a significant relationship between expression of mRNA gene Treg with TST (p = 0, 000), Treg with TST (p = 0, 000), and CD4 + with TST (p = 0, 000). Meanwhile, CD8 + was not significantly associated with TST (p = 0.118). Conclusions: It is necessary to check the expression of mRNA gene Treg, Treg, CD4 +, and CD8 + with more samples to find the mean value that shows the protective value of further TB. Highlights: The Mantoux tuberculin skin test (TST) is one of the criteria to determine whether a person is infected with Mycobacterium tuberculosis. It is often used to screen individuals for latent infection and assess rates of TB infection in a given population. tuberculin test results with induration diameter> 10 mm were positive regardless of the cause. Patients in this study were children who had been vaccinated against BCG and diagnosed with TB in their early toddler years. It was necessary to see the adaptive immune response that existed when the child was infected with TB. The main immune response that acts as protection against TB is played by cellular immunity, namely CD4 and CD8 T cells. We thought that if we could find between TST and adaptive immune response, TST could be a prior test to determine prognosis or disease progression. We found a strong correlation between immune activation and Treg cell frequency in TST positive persons. A higher Treg consentration was found in TST positive subjects. Nevertheless, local immune responses may differ from those in peripheral blood and exploring this interaction in the site of active infection will give important clues about their involvement in protection or pathogenesis . According to our studies the increased Treg cell frequency observed in the blood of people with active tuberculosis is likely a response to inflammation and bacterial burden.